Endoscopic laser‐ablation for the treatment of orthotopic and ectopic ureteroceles in dogs: 13 cases (2008‐2017). (11th February 2019) - Rogatko, Cleo P.; Berent, Allyson C.; Adams, Larry G.; Weisse, Chick W.; Bagley, Demetrius
Abstract : Background: Ureteroceles are a rare condition in dogs in which conventional treatments can result in substantial morbidity. Cystoscopic and fluoroscopic‐guided laser ablation (CLA) of ureteroceles can successfully relieve obstruction. Objectives: To describe the technique and outcomes of attempting CLA for treatment of ureteroceles in dogs. Animals: Thirteen client‐owned dogs that underwent CLA for treatment of ureteroceles. Methods: Retrospective multicentered study. Medical records were reviewed in all dogs that underwent CLA for ureterocele(s). A laser was used to extend the opening of the ureteral orifice (UO) unless surgical conversion was necessary. Data collected included signalment, clinicopathologic data, imaging, procedural findings, complications, and short‐ and long‐term outcome. Results: Thirteen dogs with 13 ureteroceles associated with 14 UOs resulting in ureteral obstruction were included. One ureterocele extended bilaterally. Treatment was initiated via retrograde cystoscopy (7 females), percutaneous perineal urethrocystoscopy (4 males), or percutaneous antegrade cystoscopy (2 males). Surgical conversion was necessary in 2 males. Ten of 14 (71%) UOs associated with the ureteroceles were ectopic. Thirteen of 14 had stenotic or imperforate UOs. No postoperative complications were noted. Preoperative incontinence or pollakiuria was present in 9 of 13 and 3 of 13 dogs and resolved in 8 of 9 and 3 of 3 dogs, respectively. Follow‐up imaging showed resolution of all ureteroceles and improved ureteral/renal pelvic dilatation. Median follow‐up time was 27 months (range, 3‐96 months). Conclusions and Clinical Importance: Cystoscopic‐guided laser ablation was effective for the treatment of ureteroceles(s) in 11 of 13 dogs.